PEREMPUAN, PENDIDIKAN DAN ARSITEK PERADABAN BANGSA - Zuhriyah, Lailatuzz (Martabat: Jurnal Perempuan dan Anak, 2018)
This article intends to explain that women have a considerable role in the effort to build a nation's civilization. So far, the stereotype that has always been attached to women is that women are only as konco wingking who have less contribution in the public sphere, so that their existence is less calculated. As second-class beings, women are considered not to need a high education because women only have role in the domestic sphere which is often referred to as the kitchen, wells and mattresses. In fact, if women are given good education, then women are quite capable of providing an extraordinary contribution to the nation. As it is believed that education functions as a driving force for social change. That means that education is the key for women to improve the quality of their lives and contribute in planning the development of a more dignified nation of civilization. In this article, we will examine how important education for women in relation to the development of national civilization.